Faktor-Faktor yang Mempengaruhi Inovasi Pendidikan: Eksplorasi pada Kebijakan, Partisipasi Masyarakat, dan Tantangan Sosial Ekonomi - Mokodompit, Multi; Abubakar, Abubakar; Bagea, Ishak; Fatmawati, Titi (Journal of Leadership, Management and Policy in Education, 2024)
This study aims to analyze the factors influencing educational innovation in Bahodopi District, Morowali Regency. The research focuses on government policy support, community participation, resource limitations, and the socio-economic conditions of the local community in implementing educational innovations. A qualitative research method with a case study approach was employed. Data were collected through interviews, observations, and documentation involving policymakers, educators, and local community members. The findings reveal that government policies, both at the central and regional levels, play a strategic role in creating a framework that supports educational innovation. Community participation, through financial support and volunteer efforts, also strengthens the implementation of educational programs. However, challenges such as limited resources and infrastructure, as well as socio-economic conditions, hinder the optimization of educational innovation. Therefore, collaboration among the government, community, and other stakeholders is necessary to overcome these challenges and enhance the quality of education in the region.